Genomic and physiological plasticity in natural variants of commercial soybean inoculants supports the non-GMO status of base-edited inoculants - Cardillo, Maria Eugenia; Brambilla, Silvina Maricel; Liebrenz, Karen Ivana; Frare, Romina Alejandra; Maguire, Vanina Giselle; Soto, Gabriela Cynthia; Ruiz, Oscar Adolfo; Ayub, Nicolás Daniel (Springer, 2025)
The regulatory classification of genome-edited microorganisms remains a topic of debate, particularly in the agricultural sector. In this study, we analyze the genomic and physiological differences of commercial variants of Bradyrhizobium japonicum E109, a widely used soybean inoculant, to establish a reference framework for distinguishing natural genetic variation from intentional genome editing. Specifically, we conducted whole-genome sequencing and phenotypic assessments of E109 variants obtained from commercial inoculants, comparing them to the official strain maintained by INTA. Our results reveal that commercial variants naturally accumulate multiple single-nucleotide substitutions, with an average of 9.7 mutations per variant, comparable to a CRISPR base-editing event targeting at least 6 different loci. Notably, the majority of these mutations occur within coding sequences (91%), and most of them (82%) are non-synonymous, potentially affecting protein function and inoculant fitness. In vitro and in planta assays confirmed that these natural mutations impact key traits, including oxidative stress resistance, root attachment, cell survival, and nitrogen fixation efficiency. These findings provide a scientific basis for regulatory decisions by demonstrating that genomic variability within commercial inoculants is a natural process and support the classification of base-edited inoculants as equivalent to non-genetically modified organisms (non-GMOs).